Structural Influence of Arabic and Persian on the Northwestern Indo-Aryan Languages - Bubenik, Vit (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
The structural influence of Classical Arabic and literary/spoken Persian on Hindi-Urdu and other Indo-Aryan (IA) languages falls into the category of slight structural borrowing. Stronger structural influence is to be expected in the westernmost IA languages, Sindhi and Lahnda, spoken in the areas where the natives were exposed to spoken Arabic already in the 8th c. They are unique among the other IA languages in attaching pronominal clitics to nouns, verbs and in colloquial Sindhi even to post-positions. Some effort will be made to sort out several factors: Dardic substrate, grammatical borrowing from Arabic and Persian, pan-IA innovations and the influence of Hindi-Urdu.